Analisis Peran Dan Dampak Tengkulak Dalam Penentuan Harga Pepaya Saat Panen Raya Di Kabupaten Boyolali: Analisis Peran Dan Dampak Tengkulak Dalam Penentuan Harga Pepaya Saat Panen Raya Di Kabupaten Boyolali - Ani Septia Sari; Retna Dewi Lestari; Setyo Rahyunanto (Universitas Duta Bangsa Surakarta, 2026)
This study aims analyze the role of middlemen in determining papaya prices during the peak harvest season in Boyolali Regency and evaluate their impact on papaya prices. The main variables studied include papaya prices, the role of middlemen, sales volume, and distribution costs. Data collection was conducted through surveys, interviews, and documentation, involving respondents consisting of farmers, middlemen, and traders. This research method used descriptive analysis based on interview data, supplemented by multiple linear regression analysis with respondent data that assessed middlemen play a significant role in determining papaya prices, both positively and negatively. The results showed that the majority of farmers, approximately 94.28%, stated that middlemen have a dominant influence in determining papaya prices. This results in farmers receiving lower selling prices than market prices due to the oligopsony distribution mechanism. Although middlemen help facilitate the distribution of harvests, this actually weakens farmers' position in negotiations. Therefore, an institution that represents farmers as well as government policies in managing papaya cultivation are needed to create a fair pricing mechanism.